New business keeps flea market going - Ferrendelli, Betta (Raton Range Raton, New Mexico, 1991)
Article on the continuation of a flea market and more on First Street.
Newspaper Article
Master List item # 90
File location is in the Raton File Cabinet
Keywords: Miller, Ben; First Street Flea Market; Business History; Local Business; Flea Markets; Socializing; First Street -- Raton, New Mexico